LA MOTIVACION EN EL DESARROLLO DE LOS RECURSOS HUMANOS DE LA ILUSTRE MUNICIPALIDAD DEL CANTON SANTO DOMINGO. - MARICELA PORTILLA ZAMBRANO (2005)
THE MOTIVATION IN THE DEVELOPMENT OF THE HUMAN RESOURCES OF THE ILLUSTRATED MUNICIPALITY OF THE SANTO DOMINGO CANTON.